The airfreight services and airfreight forwarding business at Bayan Lepas Airport, Penang - Chong, Yoon Choi (Universiti sains malaysia, 1982)
This report is prepared based on the survey which was carried out at Rayan Lepas Airport, Penang, from April, 1980 to November, 1980. This survey was carried out as a form of academic exercise which is a compulsory course for all Geography major (without education).